In situ hydrosilane reduction and preparation of gold nanoparticle–gel glass composites with nonlinear optical properties. Issue 21 (30th April 2018) - Yu, Dajiang; Sun, Xingming; Chen, Xin; Ma, Wencan; Sun, Jibin; Zhou, Chuanjian; Xie, Zheng; Zhou, Shuyun
Abstract : Gold nanoparticles were reduced in situ by a new hydrosilane reductant in organosilicon oligomer to fabricate nonlinear optical limiting materials. Abstract : Gold nanoparticle (AuNP)–gel glass composites were prepared on a carboxyl organosilicon oligomer by an in situ method using hydrosilane as a reductant. The organosilicon oligomer stabilized AuNPs, and hydrosilane directly bonded to the oligomer after the reducing reaction. The reaction and samples were characterized by FT-IR spectroscopy, UV-vis absorption spectrometry, UV-vis-NIR transmission spectrometry, TEM, EDS, XPS and SEM. Meanwhile, the nonlinear optical limiting properties of the AuNP–gel glass composites were investigated using the Z-scan technique and optical limiting measurements, and these composites exhibited broadband nonlinear optical limiting properties (532 nm and 1064 nm). This new reductant is a promising candidate for in situ preparation without the need for extra stabilizing agents or removal of residue byproducts, and the generated particles exhibited uniform size and distribution, providing a new insight into the preparation of metal–polymer nanocomposites.